2004
DOI: 10.1111/j.1475-4932.2004.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Auction Price Anomalies: Evidence from Wool Auctions in Australia*

Abstract: Using detailed Australian wool auction data we test for further evidence of pricing anomalies at sequential auctions. We find that an anomaly frequently exists and order is frequently endogenously determined. Moreover, prices increase through some sales and decrease through others. We examine whether it is possible to explain the variation in the anomaly across sales and conclude that there is no systematic relationship between the direction of the price anomaly and the characteristics of the wool or the aucti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Among them are Neil Gandal (1997) for Israeli cable television licenses, and Stephen Donald, Harry Paarsch, and Jacques Robert (1997) for Siberian timber-export permits. Chris Jones, Flavio Menezes, and Francis Vella (1996) found that prices could increase or decrease in sequential auctions of wool, as did Chanel, Gerard-Varet, and Vincent (1996) for watches; Milgrom and Weber (1982b) show theoretically that if bidders' valuations are affiliated, then prices will tend to rise over time in a sequence of auctions of identical objects. George Deltas and Georgia Kosmopoulou (2001) find in a sale of library books that expected prices increase over the auction, but that probability of sale decreases.…”
Section: The Declining Price Anomalymentioning
confidence: 89%
“…Among them are Neil Gandal (1997) for Israeli cable television licenses, and Stephen Donald, Harry Paarsch, and Jacques Robert (1997) for Siberian timber-export permits. Chris Jones, Flavio Menezes, and Francis Vella (1996) found that prices could increase or decrease in sequential auctions of wool, as did Chanel, Gerard-Varet, and Vincent (1996) for watches; Milgrom and Weber (1982b) show theoretically that if bidders' valuations are affiliated, then prices will tend to rise over time in a sequence of auctions of identical objects. George Deltas and Georgia Kosmopoulou (2001) find in a sale of library books that expected prices increase over the auction, but that probability of sale decreases.…”
Section: The Declining Price Anomalymentioning
confidence: 89%
“…The combined presence of the two e¤ects may help explaining the more complex price paths, with prices increasing between some rounds and decreasing between others, that we sometimes observe in the data (e.g., see Jones et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Prices may decline even if there are informational externalities. In fact, the presence of both aversion to price risk and informational externalities could help explaining why in some auctions prices decline and in other they increase; it could also help explaining why in some multiple round auctions prices decline between some rounds and increase between other rounds (e.g., see Jones et al 2004). …”
Section: A Calibrated Examplementioning
confidence: 99%
See 1 more Smart Citation
“…For example, McAfee and Vincent [1993] consider the possibility of risk aversion, while von der Fehr [1994] explores the effects of participation costs. Jones et al [2004] study Australian wool auctions and detect a statistically significant price change over the course of an auction approximately thirty percent of the time. Surprisingly, when there is a change, it is just as likely to be positive as negative, and no properties of the auctions appear sufficient to predict this effect.…”
Section: Sequential Auctionsmentioning
confidence: 99%